2021
DOI: 10.1007/s00420-021-01669-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with emotional exhaustion in healthcare professionals involved in the COVID-19 pandemic: an application of the job demands-resources model

Abstract: Purpose The purpose of the present cross-sectional study is to investigate the role of perceived COVID-19-related organizational demands and threats in predicting emotional exhaustion, and the role of organizational support in reducing the negative influence of perceived COVID-19 work-related stressors on burnout. Moreover, the present study aims to add to the understanding of the role of personal resources in the Job Demands-Resources model (JD-R) by examining whether personal resources—such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 54 publications
10
80
0
3
Order By: Relevance
“…Along these lines, more than 50% of the nursing personnel felt low or not satisfaction with the health management of COVID-19, and 72% perceived a lack of resources and restrictions, mainly in the beginning of pandemic. In agreement with our data, previous studies in other demographic regions have confirmed the nurses' perceptions of organizational barriers related to heavier workloads (Manzano García & Ayala Calvo, 2021), more working hours, lack of resources (Barello et al, 2021) and more risky and stressful environment, which were related to professional commitment (Duran et al, 2021) and burnout syndrome (Galanis et al, 2021;Giménez-Espert et al, 2020). Although the lack of protective resources and professional training in the management of COVID-19 patients seems to have been resolved, job demands continue to be overwhelming.…”
Section: Discussionsupporting
confidence: 92%
“…Along these lines, more than 50% of the nursing personnel felt low or not satisfaction with the health management of COVID-19, and 72% perceived a lack of resources and restrictions, mainly in the beginning of pandemic. In agreement with our data, previous studies in other demographic regions have confirmed the nurses' perceptions of organizational barriers related to heavier workloads (Manzano García & Ayala Calvo, 2021), more working hours, lack of resources (Barello et al, 2021) and more risky and stressful environment, which were related to professional commitment (Duran et al, 2021) and burnout syndrome (Galanis et al, 2021;Giménez-Espert et al, 2020). Although the lack of protective resources and professional training in the management of COVID-19 patients seems to have been resolved, job demands continue to be overwhelming.…”
Section: Discussionsupporting
confidence: 92%
“…These have been exacerbated by a lack of knowledge and information, rapidly changing procedures, and concerns about lack of personal protective equipment, staff shortages, and risk of infection for themselves and their families [ 1 , 4 , 5 , 6 , 7 ]. Consistent with evidence on the negative psychological impact of previous epidemics on HCPs [ 8 ], there have been reports of mental distress and mental exhaustion among staff [ 1 , 9 ] with a high prevalence of anxiety, depression and insomnia among HCPs during COVID-19 [ 10 ].…”
Section: Introductionmentioning
confidence: 69%
“…Increasing job resources and support to build individual HCPs resilience could buffer long-term impacts on both staff psychological wellbeing and care quality. This has been reflected in studies underpinned by the Job-Demands Resource model [ 9 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the factors linked to the JD-R theory are job demands (i.e., teaching, assessing students, and researching while observing social distancing), which would impel academics to engage in PA or sedentary behavior associated with work. Some researchers (Barello et al, 2021;Meyer et al, 2021) have reasoned based on the JD-R theory that job demands would be more than resources in social distancing contexts. That is, an imbalance between demands and resources (i.e., demands being stronger than resources) is more probable in a social distancing setting because stress and related health risks can outplay the limited resources such as social support and selfefficacy available.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…To add, academics with limited resources would feel obligated to perform job tasks in response to adapted practices from their universities for some reasons. First, thousands of job losses due to COVID-19 were reported during the pandemic (Blackmore, 2020;Barello et al, 2021); hence, rational academics would want to stick to their jobs and satisfy their employees even if they have limited resources and face psychological problems. Secondly, academics may engage in job tasks in the post-COVID-19 era to avoid boredom or psychological problems from COVID-19 that qualify as cues to PA.…”
Section: Theoretical Frameworkmentioning
confidence: 99%